2019
DOI: 10.1108/jmtm-01-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Digital services governance: IT4IT™ for management of technology

Abstract: Purpose The purpose of this paper is to present, analyse and demonstrate the impact and potentials of a pragmatically derived information technology (IT) governance framework, IT4IT™, for the discipline of management of technology (MoT) especially within the IT industry. Design/methodology/approach This paper is based on an extensive literature study working with the limitations of the relatively recent publication of IT4IT™ and the normative character of IT4IT™. A mixed-method case study is presented based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…Monteiro et al (2019) and Saunila et al (2019) expound the problems of customer engagement in digital environment. Tambo and Filtenborg (2019) works out how IT4IT framework (see footnote 3) is linked to MoT;and Botha (2019) discusses whether intelligent machines will be capable to innovate in the future. Table I gives an overview of all eight articles about the core idea of the paper, the research questions, the applied methodology of the analysis, the main results, shortly about the contribution to MoT, and a classification for this analysis.…”
Section: Methods and Summary Of The Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Monteiro et al (2019) and Saunila et al (2019) expound the problems of customer engagement in digital environment. Tambo and Filtenborg (2019) works out how IT4IT framework (see footnote 3) is linked to MoT;and Botha (2019) discusses whether intelligent machines will be capable to innovate in the future. Table I gives an overview of all eight articles about the core idea of the paper, the research questions, the applied methodology of the analysis, the main results, shortly about the contribution to MoT, and a classification for this analysis.…”
Section: Methods and Summary Of The Papersmentioning
confidence: 99%
“…She works out customer-based and context-based factors during the back-end phase. Tambo and Filtenborg (2019) ask the following question: How should the IT4IT™ framework[3] be interpreted as an MoT framework, with respect to the dualism of IT as both innovation driver of the business, but also IT as focal in development and operational resources spend in the organisation? While conducting an analysis of the IT4IT TM framework for MoT, a literature study, and a case analysis they found that the IT4IT framework supports value creation and uses value streams will align IT better with manufacturing and services.…”
Section: Rq3 Which Factors Can Augment the Adoption Process?mentioning
confidence: 99%
See 1 more Smart Citation
“…IT must be managed and structured along defined value chain processes, life cycles, service propositions, customer interactions, and cost control like any other area of the organization so as to measure performance or service quality and align company strategy and standard operating procedures with best practices. This is known as IT Governance which can function as a risk-based controller and with difficulty withstand static technology without losing competitive momentum (Tambo & Filtenborg, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of existing academic libraries, competent management, technological plans and applications, skills workforce, joint projects and effective services are crucial. Human resources organizations, technical capabilities, competent managers and employees ensure efficiency and effectiveness (Tambo and Filtenborg, 2019). Besides, competence means the management and technical capabilities needed to understand the performance of library personnel.…”
Section: Introductionmentioning
confidence: 99%